Isolation and characterization of toxin A excretion-deficient mutants of Pseudomonas aeruginosa PAO1. - Hamood, A N (1992)
We have isolated and characterized four toxin A excretion-deficient mutants of Pseudomonas aeruginosa PAO1. Similar to previously described mutants (B. Wretlind and O. R. Pavlovskis, J. Bacteriol. 158:801-808, 1984), the mutants appear to have a pleiotropic defect in the excretion of several extracellular products, including toxin A, elastase, alkaline phosphatase, and phospholipase C. However, the mutants are not defective in the excretion of either alkaline protease or exoenzyme S. We also examined the localization and processing of toxin A in these mutants by using pulse-labeling experiments. Mature toxin A was found to be localized to the membranes only. Our results suggest that toxin A is localized to the outer membrane but is not exposed to the extracellular surfaces of the outer membranes. The results also suggest that toxin A obtained from the excretion-deficient mutants has intact disulfide bonds.